Measuring Freedom of Information: Issues and Opportunities from an Expert Survey - Giannone, Diego; De-Frutos-García, Ruth Ainoa (George Washington University, 2016)
This study describes some relevant but neglected issues in measuring freedom of information. A questionnaire was administrated to 36 international experts. Then we conducted 18 in-depth interviews with some experts to evaluate relevant issues that emerged from the questionnaire. We find that ideological, theoretical, and financial issues affect the three most important instruments for measuring freedom of information: the Freedom of the Press Index by Freedom House, the World Press Freedom Index by Reporters Without Borders, and the Media Sustainability Index by the International Research and Exchange Board. The study constitutes a preliminary step for future research to address these issues and improve the instruments.
Keywords: Libertad de información - Medición; Libertad de imprenta; Medios de comunicación social; Freedom of information; Freedom House; Reporters Without Borders; IREX; Indicators; Measurement; Media